Using Research in the Classroom to Identify and Support Vulnerable Children - Kelly, Bridgett E. (My University, 2016)
For the past two years I have been a part of the Trauma Research, Education, & Consultation at Kansas State University (TRECK) research team and the Restore Coalition. TRECK is a division of the Kansas State University College of Human Ecology, and the Restore Coalition exists to serve victims of human trafficking by identifying issues with current services for victims and adjusting those programs. I have conducted qualitative and quantitative research on the needs of victims of human trafficking, as well as how current services could be improved. This research is ongoing and a conclusion has yet to be obtained. Nevertheless, I have learned a vast amount in my time conducting this research that will benefit me in my future career as an elementary teacher. Teachers can apply the process of research to questions of learning, curriculum, or assessment in order to identify instruction and strategies that most benefit their students (Logan, 2014). I have gained knowledge of the research process and the ability to implement it in my classroom, as well as a greater understanding of the vulnerability of children when it comes to risk factors for human trafficking. In my profession, I plan to use these skills in order to use research-based evidence to identify at-risk youth and prevent them from becoming victims of human trafficking.